FINDING A PLACE AT HOME: THE TRC AS A MEANS OF (R)EVOLUTION IN PRE-SERVICE (SCIENCE) TEACHER EDUCATION - Wiseman, Dawn (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2018)
This paper focuses on how I have been attending to the TRC’s calls to action within science teacher education. It draws on personal experiences, my dissertation, Canadian policy regarding Indigenous education, and academic literature to explore what the calls ask of teacher educators. Throughout, I consider how Indigenous and Western ways of knowing, being, and doing might circulate together in specific places, and the role that Land and the natural world might play in reconciliation via science teacher education. Ultimately, the paper offers a still-in-process glimpse into how I have found a place at home to begin engaging with the Calls to Action of the TRC in science teacher education.